Digitalization and Economic Growth: Business Strategies in The Asean Market - Sendy Watazawwadu’ Ilmi; Fuad Wahdan Muhibuddin; Alfa Chasanah; Tanti Novianti (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The increasing adoption of digital technologies has initiated a fundamental restructuring of economic landscapes worldwide, including ASEAN. The diffusion of mobile connectivity and expanded internet accessibility has not only reinforced market synthesis but also fostered technical innovation and productivity improvement.Purpose: This study examines the impact of digitalization, measured by mobile subscription and internet users, on economic growth in ASEAN countries.Design/methodology/approach: Utilizing a panel dataset comprising 10 ASEAN member countries from 2010 to 2022, this approach facilitated the assessment of the relationship between digitalization and GDP per capita and other control variables, namely trade openness, investment, and inflation.Findings/Results: The analysis indicates a statistically significant positive correlation between mobile subscriptions and internet users to GDP per capita, underscoring the crucial role of digital connectivity in fostering economic efficiency, market expansion, and innovation. Furthermore, trade openness demonstrates a beneficial effect on economic growth. Conversely, inflation demonstrates a significant negative impact on growth. Investment demonstrates no substantial effect, indicating variations in investment quality and distribution among ASEAN nations.Conclusion: The findings of this study emphasize the pivotal role of digitalization, and particularly internet penetration, in enhancing economic performance. These findings highlight the need for focused investments in telecommunications infrastructure in order to successfully promote innovation and productivity growth throughout the area.Originality/value (State of the art): This study contributes to the existing literature by integrating business perspective to offer novel insights into the interplay between digitalization, trade, and economic performance. The findings provide valuable implication for both policymakers and business leaders. Keywords: ASEAN, business economics, business strategy, digitalization, economic growth